Does Indonesia’s SDGs bonds allocation maximize economic returns through high multiplier sectors? - Rahman, Rheza Auliya; Akhmadi, Muhammad Heru (Universitas Muhammadiyah Yogyakarta, 2025)
The financing gap in achieving the Sustainable Development Goals (SDGs) 2030 has led the Government of Indonesia to issue thematic government securities, known as SDGs Bonds, as an innovative financing alternative. The economic effectiveness of this instrument, nevertheless, remains a critical issue. The objective of this study is to evaluate the economic impact of SDGs Bonds allocations during the 2021–2023 period. To this end, an Input-Output (IO) approach with the RAS adjustment method was employed. The analysis demonstrated that SDG Bonds have been systematically allocated to social sectors, namely education, health, and social protection, selected for their high absorption capacity and robust development narratives. Despite this focus, IO analysis revealed that the economic impact extends to 52 sectors, as marked by significant increases in gross value added (GVA) and aggregate income each year. However, it has been estimated that approximately 2 to 3% of the impact flows into sectors not aligned with sustainability principles, and there is unrealized GVA potential ranging from 2.3% to 5.41% due to suboptimal allocation to high-multiplier sectors. Policy simulations suggest that increased allocations to social sectors, when not balanced with sectoral efficiency considerations, can lead to greater unrealized economic potential. Consequently, a sectoral IO-based approach should be considered as a complementary tool in the project selection process. This integration has the capacity to facilitate financing decisions that are not only socially driven but also economically impactful and sustainable in the long term.